Nuns and soldiers - Murdoch, Iris, ....- (Harmondsworth : Penguin, 1987)
Gertrude has lost her husband and Anne, an ex-nun, her God. They plan to live together and do good works. The 'Count', a Polish man in exile watches over Gertrude with loving patience. Tim, a failed painter, plans with his punk girlfriend to live off his rich friends. Who will judge whom in this intricate pattern of love and deceit?
Keywords: Fiction